Evidence of cardiac functional reserve upon exhaustion during incremental exercise to determine VO2max. Issue 2 (4th January 2013) - Elliott, Adrian D; Skowno, Justin; Prabhu, Mahesh; Noakes, Timothy David; Ansley, Les
Abstract : Background: There remains considerable debate regarding the limiting factor(s) for maximal oxygen uptake (VO2max ). Previous studies have shown that the central circulation may be the primary limiting factor for VO2max and that cardiac work increases beyond VO2max . Aim: We sought to evaluate whether the work of the heart limits VO2max during upright incremental cycle exercise to exhaustion. Methods: Eight trained men completed two incremental exercise trials, each terminating with exercise at two different rates of work eliciting VO2max (MAX and SUPRAMAX). During each exercise trial we continuously recorded cardiac output using pulse-contour analysis calibrated with a lithium dilution method. Intra-arterial pressure was recorded from the radial artery while pulmonary gas exchange was measured continuously for an assessment of oxygen uptake. Results: The workload during SUPRAMAX (mean±SD: 346.5±43.2 W) was 10% greater than that achieved during MAX (315±39.3 W). There was no significant difference between MAX and SUPRAMAX for Q (28.7 vs 29.4 L/min) or VO2 (4.3 vs 4.3 L/min). Mean arterial pressure was significantly higher during SUPRAMAX, corresponding to a higher cardiac power output (8.1 vs 8.5 W; p<0.06). Conclusions: Despite similar VO2 and Q, the greater cardiac work during SUPRAMAX supports the view that the heart is working submaximally at exhaustion during an incremental exercise test (MAX).